Presence and molecular characteristics of oxazolidinone resistance in staphylococci from household animals in rural China. (7th February 2018) - Sun, Chengtao; Zhang, Peng; Ji, Xing; Fan, Run; Chen, Baoli; Wang, Yang; Schwarz, Stefan; Wu, Congming
Abstract: Objectives: To investigate the presence and molecular characteristics of oxazolidinone resistance genes cfr and optrA in staphylococci from household animals in rural China. Methods: Various samples were collected from household animals in 12 rural villages. Staphylococcal isolates showing florfenicol MICs ≥10 mg/L were identified and screened for the presence of cfr and/or optrA . PCR-positive isolates were characterized by antimicrobial susceptibility testing, S1 nuclease PFGE and Southern blotting. WGS data were analysed to identify the core-genome phylogenetic profile of each isolate as well as the genetic environment of cfr and/or optrA . Results: Nine optrA -positive (seven Staphylococcus sciuri and two Staphylococcus simulans ) and 10 cfr -positive staphylococci were identified from eight and five villages, respectively. The gene optrA was chromosomally encoded in all nine isolates, whereas cfr was located on a plasmid in one S. sciuri and three Staphylococcus saprophyticus and in the chromosomal DNA of single Staphylococcus cohnii and Staphylococcus lentus isolates and two S. sciuri isolates. The remaining two cfr -carrying Staphylococcus haemolyticus isolates were indistinguishable by PFGE. Most optrA - or cfr -carrying staphylococci also harboured phenicol, tetracycline and/or macrolide-lincosamide-streptogramin B resistance genes. Genetic environment analysis showed that, for the first time, optrA was associated with transposon Tn 6261, while cfr was adjacent to both a tnp (transposase) gene and a Tn 558 transposon. Conclusions: The current study reveals for the first time the wide distribution of oxazolidinone resistance genes optrA and cfr in household animals in rural areas of China and is the first identification of optrA in S. simulans isolates.